(untitled) (Rupandehi Campus Journal, 2022)
The present study aims to find out the “Teachers’ Perception Towards Pre and Post-Teaching Activities in English Language Teaching”. The main focus of the study was directed on perception of higher level English teacher towards pre and post-teaching activities in English Language Teaching. The study, being an attitudinal study, is believed to be relevant in offering a realistic picture of the effectiveness of pre and post- teaching activities in ELT. The study was carried out using both primary and secondary sources of data. For primary data, firstly higher-level English teachers have been selected through random sampling procedure. The study was confined with in Rupandehi district to find out the effectiveness of pre and post- teaching activities in ELT. It was found that the higher-level teachers are highly positive towards the teachers’ pre and post-teaching activities in ELT.